MODELING THE SYNCHRONIZATION OF PRESENTATION SYSTEM USING SYNCHRONIZED MULTIMEDIA INTEGRATION LANGUAGE DRIVEN APPROACH - ASNAWI, RUSTAM (2012)
Currently various live multimedia presentation (LMP) applications are available. Unfortunately, in LMP there is no established-standard model for the synchronization as well as in stored multimedia presentation (SMP) with its Synchronized Multimedia Integration Language (SMIL). Meanwhile, the development of the common PSs, as an integral part of LMP, departed from the drawbacks of the slideware application. Hence they are designed as slide based oriented with dual or multi display features. However, increasing the complexity of the content and style of the multimedia presentation will impact on the synchronization problem when presenting various multimedia data either synchronization with temporal and spatial constraints. The aim of this research is to address some weaknesses and problems in common PS models especially related with the shortcoming of slide based presentation and synchronization problems. To attain this aim, synchronization models with temporal and spatial constraints of PS using SMIL-driven approach have been designed, developed, and evaluated. The methodology includes: (1) Background study; (2) designing, formalization and V &V the conceptual model using Petri Net and ERTSM; (3) application development and model evaluation using scenario based approach; (4) Results analysis and further discussion. As a result, the conceptual model has been verified & validated and already satisfied all specification requirements. Also, it has been evaluated using scenario based which reveals that the proposed model has agreed with specification requirements in application level. The contributions of this research include a conceptual model of PS (IMPS) using SMIL driven approach that has formal and synchronization models. A prototype of such PS (1M-Player) has been developed with package library of media displayers. Introducing hybrid slide and non-slide based presentation as a new concept in live presentation. Furthermore, based on the concept of IMPS and 1M-Player, a framework for general LMP applications has been derived and proposed. This can be used to develop any LMP applications for different domain areas and other various purposes.